In a cohort of individuals with type 2 diabetes using the drug sulfasalazine, HbA1c lowering is associated with haematological changes. Issue 9 (8th December 2020) - N'Dow, Samira M. S.; Donnelly, Louise A.; Pearson, Ewan R.; Rena, Graham
Abstract: Objectives: Several small studies indicate the sulphonamide component of the drug sulfasalazine lowers HbA1c. We investigated reduction of HbA1c following incident prescription of sulfasalazine and related aminosalicylates, lacking the sulphonamide group, in an observational cohort. Research Design and Methods: Individuals in the Scottish Care Information Diabetes Collaboration (SCI‐Diabetes) with type 2 diabetes and incident prescription for an aminosalicylate drug (sulfasalazine, mesalazine, olsalazine or balsalazide) were identified. Baseline and 6‐month HbA1c were required for eligibility, to calculate HbA1c response. To investigate association with haemolysis, change in components of full blood count was assessed. Paired t‐tests compared difference in baseline and treatment HbA1c measures and other clinical variables. Results: In all, 113 individuals treated with sulfasalazine and 103 with mesalazine (lacking the sulphonamide group) were eligible, with no eligible individuals treated with olsalazine or balsalazide. Baseline characteristics were similar. Mean (SD) HbA1c reduction at 6 months was −9 ± 16 mmol/mol (−0.9 ± 1.4%) ( p  < 0.0001) in those taking sulfasalazine with no reduction in those taking mesalazine (2 ± 16 mmol/mol (0.2 ± 1.4%). Sulfasalazine but not mesalazine was associated with a mean (SD) increase in mean cell volume of 3.7 ± 5.6 fl ( p  < 0.0001) and decrease in red cell count of −0.2 ± 0.4 × 10 −12 /L ( p  < 0.0001). Conclusions: In this observational, population‐based study, sulfasalazine initiation was associated with a 6‐month reduction in HbA1c . This correlated with haematological changes suggesting haemolytic effects of sulfasalazine. Haemolysis is proposed to contribute to HbA1c lowering through the sulphonamide pharmacophore. This suggests that HbA1c is not a reliable measure of glycaemia in individuals prescribed sulfasalazine.